Blending Ecosystem Service and Resilience Perspectives in Planning of Natural Infrastructure: Lessons from the San Francisco Bay Area - Hamel, Perrine; Hamann, Maike; Kuiper, Jan J.; Andersson, Erik; Arkema, Katie K.; Silver, Jess M.; Daily, Gretchen C.; Guerry, Anne D. (Frontiers in Environmental Science, 2021)
Globally, cities face massive environmental and societal challenges such as rapid population growth and climate change. In response, natural infrastructure is increasingly recognized for its potential to enhance resilience and improve human well-being. Here, we examine the role of the ecosystem services and resilience approaches in urban planning, which both aim to sustain the long-term benefits of natural infrastructure in cities. While the two approaches are intertwined and share deep roots in social-ecological systems framing, they confer complementary strengths in practice, which we illustrate with a case study in the San Francisco Bay Area, USA. We show that, at present, the main strength of ecosystem service practice is to provide actionable information, while urban resilience practice supports the development of holistic long-term strategies. We discuss operational limitations of both approaches and suggest that understanding and leveraging their complementary strengths could help bridge the implementation gap between research and practice in urban natural infrastructure planning.